EFFECTIVENESS OF DISTANCE LEARNING ONLINE AT HOME DURING THE COVID-19 PANDEMIC - Eko Lianto Rihardi; Erwan Prastiawan; Irfan Nurdiansyah (GoAcademica Research dan Publishing, 2021)
This study aims to determine the level of effectiveness of study online from home during the Covid-19 pandemic for teachers, parents and students. The method used in this research is a qualitative method which is literature study using books and other literature sources and is analyzed descriptively, namely research with reference to data collection techniques carried out by interviews, looking for data on relevant matters. Based on the research findings, it can be concluded that online learning is still not effective because of the many obstacles that occur here and there. This happens not only from the facilities and infrastructure but also the lack of readiness of both the educators, students, and parents so that the delivery of material in learning becomes less than optimal.